Effect Study of Continuous Monoculture on the Quality of Salvia miltiorrhiza Bge Roots. (28th May 2020) - Liu, Hongyan; Niu, Min; Zhu, Shu; Zhang, Fang; Liu, Qian; Liu, Yang; Liu, Ruohan; Zhang, Yongqing
Abstract : High-efficiency monoculture severely inhibits the growth of Salvia miltiorrhiza Bge and decreases the yield and quality of crude drug, thus resulting in serious economic losses in China. Here, we selected four replanted field soils with 1, 2, 3, and 4 years of monoculture history to investigate the influence of continuous monocropping soil on the property of medicinal materials by pot experiments. Results showed that the commodity appearance and active ingredient contents of Salvia miltiorrhiza were significantly affected by soil with different continuous monocropping years. Along the time series of plantation soil, the diameter of main roots, weight of fresh roots, and total contents of hydrophilic and lipophilic components demonstrated a decline tendency. With the method of PCA, the property of medicinal materials affected by continuous monocropping soil was evaluated by the following formula: F = 0.3762 × F 1 + 0.2320 × F 2 + 0.1913 × F 3 + 0.0994 × F 4 / 0.8989 . Eventually, crude drug properties ranked according to comprehensive scores were as follows: CK   0.380 > 1   year   0.360 > 2   years   0.348 > 3   years   0.337 > 4   years   0.245 . For the medicinal plant of Salvia miltiorrhiza Bge, continuous monocropping soil had significant effects on the property of Salvia miltiorrhiza and should be ameliorated by some measures. The results provide support for the optimal continuous cropping year selection and continuous cropping obstacle abatement of Salvia miltiorrhiza Bge.